Journey to Poland : documentary landscapes of the holocaust - Cinquegrani, Maurizio (Edinburgh scholarship online., 2018)
Journey to Poland addresses crucial issues of memory and history in relation to the Holocaust as it unfolded in the territories of the Second Polish Republic.